Destined for decline? Examining nuclear energy from a technological innovation systems perspective - Markard, J.; Bento, N.; Kittner, N.; Nuñez-Jimenez, A. (Energy Research and Social Science, 2020)
Technology decline is a central element of sustainability transitions. However, transition scholars have only just begun to analyze decline. This paper uses the technological innovation systems (TIS) perspective to study decline. Our case is nuclear energy, which is at a crossroads. Some view nuclear as a key technology to address climate change, while others see an industry in decline. We examine a broad range of empirical indicators at the global scale to assess whether or not nuclear energy is in decline. We find that an eroding actor base, shrinking opportunities in liberalized electricity markets, the break-up of existing networks, loss of legitimacy, increasing cost and time overruns, and abandoned projects are clear indications of decline. Also, increasingly fierce competition from natural gas, solar PV, wind, and energy-storage technologies speaks against nuclear in the electricity sector. We conclude that, while there might be a future for nuclear in state-controlled ‘niches’ such as Russia or China, new nuclear power plants do not seem likely to become a core element in the struggle against climate change. Our conceptual contribution is twofold. First, we show how the TIS framework can be mobilized to study technology decline. Second, we explore a range of indicators to cover the multiple dimensions of decline, including actors, institutions, technology, and context.